Kinetics of water sorption and sugar crystallization in freeze-dried bananas previously immersed in concentrated sucrose and trehalose solution - Iglesias, Héctor (2017)
Fil: Iglesias, Héctor. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Industrias; Argentina